JENIS KELELAWAR PEMAKAN BUAH (Pteropodidae) DI KAWASAN GUA THANG RAYA KECAMATAN BEDUAI KABUPATEN SANGGAU KALIMANTAN BARAT - Thursiana, Agustina; Nurdjali, Bachrun; Nurhaida, . (Universitas Tanjungpura, 2017)
Bats are very important for the ecosystem including for pollination as well as the spread of plants. Forest clearing for plantation becomes a threat to bats to fine food in fruits trees, specially frugivorous bats (Pteropodidae). The aim of this study is to determine the species diversity of frugivorous bats (Pteropodidae) in the area of Thang Raya Cave in Subdistrict of Beduai Sanggau Regency West Kalimantan, and the results of this study are expected to provide information about the types of frugivorous bats (Pteropodidae) that can be used in ecosystem management in the region of Thang Raya Cave. This research used the catch and release method with mist nets as many as 6 pieces. This mist nets were placed purposively at three research sites namely at the around of watershed, fruit trees and Thang raya Cave. The bats caught were measured, identified and tagged and then released. From the analysis, it is known the bats caught were as many as 31 individuals belonging to one family and two species of bat, were Rosettus amplexicaudatus and cynopterus horsfieldi with the number of individual 24 males and 7 femakes. The highest dominance indeks of bats found in the around of the Thnag Raya CafÃ© was (1,00), the indeksÂ of highest species diversity was found at of fruit trees (0,23), the evenness index was the highest at of fruit trees (0,76), the index of species richness was the highest at of fruit trees (1,05), and the similarty index was the highest at between the fruit trees and Thang Raya Cave (0,82). Keywords: Frugivorous bats (Pteropodidae) catch and release method, identification.